2015
DOI: 10.1371/journal.pone.0133598
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Nuclear Receptor Nur77 Aggravates Mouse Experimental Colitis by Increased NFκB Activity in Macrophages

Abstract: Nuclear receptor Nur77, also referred to as NR4A1 or TR3, plays an important role in innate and adaptive immunity. Nur77 is crucial in regulating the T helper 1/regulatory T-cell balance, is expressed in macrophages and drives M2 macrophage polarization. In this study we aimed to define the function of Nur77 in inflammatory bowel disease. In wild-type and Nur77-/- mice, colitis development was studied in dextran sodium sulphate (DSS)- and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced models. To understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 80 publications
(102 reference statements)
5
64
2
Order By: Relevance
“…Within this study, we demonstrate that LPS and TNFα stimulation drives gene and protein secretion of chemokines MIP-3α and MCP-1 in primary and immortalized human and murine (LPS only) myeloid cells. We further identify NF-κB to be the upstream regulator of both chemokines within these conditions and cells consistent with previous studies in myeloid and other cell types (14, 26, 29, 30). Interestingly, we observed using depleted cells that NR4A2 and 3 were positive regulators of inflammatory-driven MIP-3α in human THP-1 cells and murine RAW264.7 macrophage cells (NR4A2 only), while repressors of MCP-1 as stated above.…”
Section: Discussionsupporting
confidence: 90%
“…Within this study, we demonstrate that LPS and TNFα stimulation drives gene and protein secretion of chemokines MIP-3α and MCP-1 in primary and immortalized human and murine (LPS only) myeloid cells. We further identify NF-κB to be the upstream regulator of both chemokines within these conditions and cells consistent with previous studies in myeloid and other cell types (14, 26, 29, 30). Interestingly, we observed using depleted cells that NR4A2 and 3 were positive regulators of inflammatory-driven MIP-3α in human THP-1 cells and murine RAW264.7 macrophage cells (NR4A2 only), while repressors of MCP-1 as stated above.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Nur77 is known to regulate NF-jB and MAPKs pathways that contribute to the biological functions of Nur77 (Hamers et al 2015;Li et al 2015a;Shao et al 2016). In this study, we found that activation or overexpression of Nur77 inhibited the NF-jB activation, as evidenced by decreased transcriptional activity of NF-jB, decreased phosphorylation, and degradation of IjBa as well as the subsequent nuclear translocation of NF-jB p65 in LPS-activated microglia.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, Nur77 is known to regulate NF‐κB and MAPKs pathways that contribute to the biological functions of Nur77 (Hamers et al . ; Li et al . ; Shao et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent interest has focused on its potent anti-inflammatory effect in inflammatory diseases and cancer. Genetic studies have revealed a critical role of Nur77 in controlling the inflammatory responses, highlighted by its protective function in atherosclerosis (Hamers et al, 2012; Hanna et al, 2012), obesity (Perez-Sieira et al, 2013), diabetes (Chao et al, 2009), asthma (Kurakula et al, 2015), arthritis (De Silva et al, 2005), and inflammatory bowel disease (Hamers et al, 2015; Wu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%